Entrepreneurial Motivation of Street Vendors in Seruni Beach, Bantaeng Regency - Muhammad Darwis; Rifani Sri Wahyuni; Muhammad Guntur; Haedar Akib; Risma Niswaty (Universitas Negeri Makassar, 2020)
Motivation to develop a new business is required not only by self-confidence in its ability to succeed, but also by its ability to access information about entrepreneurial opportunities. This study aims to determine how the motivation to entrepreneurship street vendors in Seruni Beach, Bantaeng Regency. Data collection used through observation, interview and documentation techniques. Informants in the study were seven informants with the type of research and the approach used was a qualitative description. Data collection used through observation, interview and documentation techniques. The results showed that the motivation of the street vendors on Seruni Beach, Bantaeng Regency in terms of each indicator, starting from the entrepreneurial spirit indicator displayed by the street vendors, the results showed that there was indeed enthusiasm in a trader, an indicator of creativity whose results showed the traders had creativity, an innovative indicator whose results show that traders have innovative, risk-taking indicators of courage, the results show that traders are brave enough to take all kinds of risks in entrepreneurship.